Contrast-induced nephropathy after staged balloon pulmonary angioplasty: lower risk compared with left-sided cardiac procedures. (14th October 2021) - Pereira, A R; Cale, R; Ferreira, F; Alegria, S; Sebaiti, D; Martinho, M; Repolho, D; Vitorino, S; Santos, P; Loureiro, M J; Pereira, H
Abstract: Introduction: The risk of contrast-induced nephropathy (CIN) after left-sided cardiac procedures is reported as 10–15%. When the ratio of total contrast volume in ml to glomerular filtration rate (GFR) in mL/min (ratio V/GFR) exceeds 3.7, the risk increases significantly. However, there are few reports regarding the risk of CIN in patients (pts) with right-sided cardiac interventions such as balloon pulmonary angioplasty (BPA) and ratio V/GFR is not validated for use in this procedures. Purpose: To assess the prevalence of CIN in pts with chronic thromboembolic pulmonary disease with or without hypertension (CTEPH/CTED) undergoing BPA. Methods: Prospective single-centre study that included all BPA sessions performed from 2017 to 2020. Serum creatinine concentration (SC) was measured and the GFR was estimated using the Chronic Kidney Disease Epidemiology Collaboration equation (CKD-EPI) before and 48 hours after each BPA procedure and 6 months after BPA treatment completion. CIN was defined as an increase of ≥25% and/or ≥0.5 mg/dL in SC from the baseline value within 48h of contrast administration. Results: 76 consecutive BPA sessions were performed in 15 CTEPH/CTED pts: mean age 63.2±14.0 years, 60% female, 86.7% CTEPH, mean of 5.3±1.9 sessions per patient with 4.3±1.9 vessels dilated per session. Mean value of GFR before BPA program was 73.5±26.3 mL/min. All the procedures were performed using low-osmolality contrast agent with a 1:1 dilution ratio with normal saline solution. Pts received 273.0±73.0 mL of contrast per session with a ratio V/GFR 3.7±1.7 mL. SC and GFR did not change significantly within 48h after BPA (+3.1%, p=0.07 and −3.0%, p=0.13, respectively). Ratio V/GFR >3.7 occurred in 44.3% of cases (n=31), but CIN occurred in only 5.3% (n=4) with an increase in SC <0.5 mg/dL but ≥25% in 3 cases (+33% in mean) and ≥0.5 mg/dL in 1 case. None of the pts required renal replacement therapy. Higher SC and lower GFR 48h after BPA were significantly correlated with greater rato V/GFR during procedure (r=0.75, p<0.01 and r=−0.74, p<0.01, respectively) – see figure. But neither higher values of ratio V/GFR (OR 1.43; CI95% 0.84–2.41; p=0.19) nor V/GFR >3.7 (OR 1.28; CI95% 0.17–9.6; p=0.81) were predictors of CIN. GFR before procedure did not influence the contrast volume administered (p=0.901), number of vessels (p=0.63) and segments treated by session (p=0.45). At 6 months follow-up, there was a trend for SC (1.3±0.2 mg/dL vs 1.1±0.2 mg/dL, −15%, p=0.43) and GFR (44.5±8.3 mg/dL vs 53.0±12.6 mg/dL, +16%, p=0.34) improvement in pts with impaired renal function at baseline (GFR<60 mL/min). Conclusions: These findings suggested that the occurrence of CIN after BPA was low, raising the hypothesis that the influence of contrast agent on renal function could differ in right-sided cardiac interventions. Although the ratio V/GFR may be correlated with the risk of nephropathy, it is necessary to find a new cut-off to predict CIN in BPA pts. FUNDunding Acknowledgement: Type of funding sources: None.